Investigation of tractor engine power and economical working conditions utilization during transport operation - Juostas, Antanas; Janulevičius, Algirdas (Transport, 2008)
Article analyzes tractor working and its engine conditions from economical point of view. Overview of tractor wheel slippage reliance on the traction force and weight utilization coefficient is given. Tractor maximum driving force according to road and field conditions, and driving speed are submitted. Literature and theoretical investigation analysis is done, where interaction between tractor wheels made‐up driving force and grip is analysed. Driving speed and driving force dependence on rolling resistance and total aggregate weight using nominal power is described. In the present experimental research reduction in fuel consumption of tractor transport aggregate by reducing engine speed and by keeping the same work speed, was determined. First published online: 27 Oct 2010